Childhood trauma mediates the association between ethnic minority status and more severe hallucinations in psychotic disorder. Issue 1 (20th May 2014) - Berg, A. O.; Aas, M.; Larsson, S.; Nerhus, M.; Hauff, E.; Andreassen, O. A.; Melle, I.
Abstract : Background: Ethnic minority status and childhood trauma are established risk factors for psychotic disorders. Both are found to be associated with increased level of positive symptoms, in particular auditory hallucinations. Our main aim was to investigate the experience and effect of childhood trauma in patients with psychosis from ethnic minorities, hypothesizing that they would report more childhood trauma than the majority and that this would be associated with more current and lifetime hallucinations. Method: In this cross-sectional study we included 454 patients with a SCID-I DSM-IV diagnosis of non-affective or affective psychotic disorder. Current hallucinations were measured with the Positive and Negative Syndrome Scale (P3; Hallucinatory Behaviour). Lifetime hallucinations were assessed with the SCID-I items: auditory hallucinations, voices commenting and two or more voices conversing. Childhood trauma was assessed with the Childhood Trauma Questionnaire, self-report version. Results: Patients from ethnic minority groups ( n = 69) reported significantly more childhood trauma, specifically physical abuse/neglect, and sexual abuse. They had significantly more current hallucinatory behaviour and lifetime symptoms of hearing two or more voices conversing. Regression analyses revealed that the presence of childhood trauma mediated the association between ethnic minorities and hallucinations. Conclusions: More childhood trauma in ethnic minorities with psychosis may partially explain findings of more positive symptoms, especially hallucinations, in this group. The association between childhood trauma and these first-rank symptoms may in part explain this group's higher risk of being diagnosed with a schizophrenia-spectrum diagnosis. The findings show the importance of childhood trauma in symptom development in psychosis.